Viplavī Bāṅgalā, sonāra Bāṅgalā - Gokhale, Hemanta Lakshmaṇa (Puṇe : Sādhanā Prakāśana, 2021)
Articles, chiefly on political history of Bangladesh; published earlier in Sādhanā, Marathi weekly, during June to September 1971, and January to April 2021.
Also available as an e-book.
In Marathi; includes passages in Hindi.
Keywords: Bangladesh -- Politics and government -- 1971-; Bangladesh -- Social conditions; Bangladesh -- Economic conditions; Bangladesh -- Politique et gouvernement -- 1971-; Economic history; Politics and government; Social conditions; Bangladesh; Since 1971